History and current use of feed additives in the European Union: legislative and practical aspects - Doeschate, R. A. H. M. ten; Raine, H (Avian gut function in health and disease, 2006)
Whilst the term feed additives encompasses a variety of products, this chapter will concentrate on product groups such as antibiotic growth promoters, coccidiostats and enzymes. These products have been, and are, subject to scrutiny and licensing at European Union (EU) and national level. The history of antibiotic growth promoters serves as a case study for the development of a product group, ensuing legislation, pressure group activity and the subsequent demise of the product group. EU legislation has evolved over the years from a situation of limited scope and relatively relaxed rules to the current system where the scope is being extended to more products and with stricter rules. The current EU regulation (1831/2003) is based on the precautionary principle related to human health, animal health and the environment. At present there are signs that legislation has tightened to such a level that certain products are not available on the EU market, maybe as a result of high costs or delays, due to the registration process. A balance needs to be found between effective legislation regulating the safe use of additives and allowing new product and concept development. From a practical nutritionist's point of view the whole area is very complicated, with several products on the market, and it is unclear whether they are additives in the legal sense or not, but there is a responsibility on the nutritionist to ensure compliance with the law. With antibiotic growth promoters disappearing, several 'replacement' products need to be evaluated, which is another big challenge for nutritionists.